The gut microbiota in high-altitude medicine: intersection of hypoxic adaptation and disease management - Chen, Qian; Huang, Demei; Liu, Junling; Jia, Nan; Shen, Zherui; Pei, Caixia; Chen, Chen; Liu, Yuhan; Wang, Yilan; Shi, Shihua; Yi, Renxing; He, Yacong; et al. (Frontiers in Microbiology, 2025)
High-altitude exposure impacts hundreds of millions globally, posing a unique health challenge due to extreme stressors including hypobaric hypoxia and intense ultraviolet radiation. The gut microbiota, a microbial community residing in the intestinal tract, plays a pivotal role in maintaining host health through homeostasis. Emerging evidence highlights the gut microbiome's dual roles in facilitating host adaptation to high-altitude environments and in mediating maladaptive responses. This review explores the potential changes and mechanisms of the gut microbiota and its metabolites in mediating host adaptation and pathogenesis related to high-altitude exposure, alongside summarizing effective strategies for targeted microbiota modulation to prevent and treat altitude-related disorders. Furthermore, we discuss the influence of microbiota on drug metabolism in high-altitude populations and its potential role as diagnostic and prognostic biomarkers. Although current research remains exploratory, the gut microbiome has garnered significant interest in high-altitude medicine. With advancing investigations, microbiota-targeted interventions may emerge as critical breakthroughs for altitude disease management, paving the way for improved human adaptation to extreme environments and precision health strategies for plateau populations.